PROBLEMATIKA YURIDIS SISTEM ALOKASI HUKUM DALAM PENGAWASAN HAKIM - Muhtadi Muhtadi (Universitas Lampung, 2015)
The procedure Oversight Judge (How It Treats People) is regulated by an internal mechanism by the Supreme Court as an institution builder through the remedies and oversight mechanisms of behavior, as well as the external monitoring Judicial Commission behavior of justices and judges in the Supreme Court. While the constitutional judges monitored internally without the involvement of outside agencies. There is injustice setting norms supervision of judges (How It Distribute). If the justices and courts in Supreme Court monitored externally by Judicial Commission and internally by the Supreme Court, Court only supervised institution's own internal artificial. Keywords: Judge Supervision, and System Allocation Law